GLP-1 analogs in the treatment of obesity - Metelska, Aleksandra; Metelski, Jakub; Sereda, Dominika; Nieścior, Hubert (Journal of Education, Health and Sport, 2022)
Introduction and purpose Obesity is a chronic disease that causes the development of numerous complications such as cardiovascular disease, cancer and type 2 diabetes. The 2017 global nutrition report showed that 2 billion adults and 41 million children worldwide are overweight or obese. Due to the growing problem of obesity, pharmacotherapy is recommended in patients with BMI ≥30 kg / m2 or BMI> 27 kg / m2 with accompanying risk factors. The aim of the study is to discuss the role of GLP-1 analogues in the treatment of obesity. Description of the state of knowledge GLP-1 receptor agonists that were initially related to the treatment of type 2 diabetes are now being used successfully in the treatment of obesity. The GLP-1 hormone is released from intestinal enteroendocrine cells in response to an increase in glucose levels. Due to the wide neuroanatomical distribution of GLP-1R within the structures of the reward system, it is possible to suppress the need for food intake, which translates into a reduction in the amount of food consumed and a decrease in body weight. The most common side effects associated with the use of GLP-1 analogues include gastrointestinal symptoms such as nausea, vomiting, diarrhea and constipation, which rarely lead to discontinuation of treatment. Summary Numerous studies have shown that chronic systemic delivery of GLP-1 agonists led to weight loss and helped to maintain a lower body weight. Reduction in food intake is reported as the main mechanism. Discontinuation of the drug was associated with weight gain.